TRADITIONAL KNOWLEDGE ON ECOLOGY IN JAVANESE CHILDREN’S LITERATURE - Herminingrum, Sri; Sukmawan, Sony (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this text-oriented study is to reveal traditional knowledge of ecology in children’s literature with the possible use for introducing children to the environment. Eco-criticism and functionalism are employed as integrated approaches to search for the teachings on environmental sustainability such as a harmonious life in nature, environment preservation, and the life cycle of plants and animals. The objects of the study are three Javanese children’s stories: ‘It’s Better to be a Rabbit’ (‘Luwih Becik Dadi Truwelu’), ‘Flower, Butterfly, Caterpillar, and Leaf’ (‘Kembang, Kupu, Uler, lan Godhong’), and ‘The Arrogant Cecen’ (‘Cecen Sing Gumedhe’). These fables are examined intrinsically, therefore, content analysis becomes a theoretical anchor. Considering the sampled stories are original tales, the values of local wisdom on how to protect ecological systems can be distilled as a directive tool for shaping children’s moral-ethics and guiding them to live in harmony with their surrounding nature. Thus, traditional knowledge learned from those stories is not solely a means of legitimizing cultural traditions and educating children to love the environment, but, supposedly, they also serve as materials for storytelling because of the characteristics of each tale itself being interesting and entertaining.